The economics of financial cooperatives : income distribution, political economy and regulation - Khafagy, Amr (London : Routledge, 2019)
Building on theories of finance and distribution, and the political economy of finance, this book explains the influence of financial cooperatives on wealth and income distribution, and institutional factors that determine the development of financial cooperatives. The book discusses the dynamics of income and wealth distribution with and without financial cooperatives, and defines the economic objective for financial cooperatives. Through explaining the influence of political institutions and regulations on the development of financial cooperatives, this book examines why financial cooperatives grew in some emerging economies and not in other similar ones. The book is of interest to scholars interested in financial economics, political economy of finance, alternative banking and development finance, and banking regulation. The book also gives valuable output to central bankers and financial and monetary policy makers in underdeveloped economies. In addition, it will be of particular interest to practitioners in international development institutions, especially those engaged in development finance and rural finance.
"Building on theories of finance and distribution, and the political economy of finance, this book explains the influence of financial cooperatives on wealth and income distribution, and institutional factors that determine the development of financial cooperatives. The book discusses the dynamics of income and wealth distribution with and without financial cooperatives, and defines the economic objective for financial cooperatives. Through explaining the influence of political institutions and regulations on the development of financial cooperatives, this book examines why financial cooperatives grew in some emerging economies and not in other similar ones. The book is of interest to scholars interested in financial economics, political economy of finance, alternative banking and development finance, and banking regulation. The book also gives valuable output to central bankers and financial and monetary policy makers in underdeveloped economies. In addition, it will be of particular interest to practitioners in international development institutions, especially those engaged in development finance and rural finance"--
1. Introduction: why financial cooperatives matter now2. Finance, distribution and the economic objective of financial cooperatives 3. Financial cooperatives and income inequality: empirical evidence 4. Political economy theory for financial cooperative development5. Political institutions and financial cooperative development: empirical evidence 6.The origin and rationale for financial cooperative regulation in underdeveloped economies 7. Regulation, supervision and deposit insurance for financial cooperatives: an empirical investigationDiscussion and conclusions
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Finance; BUSINESS & ECONOMICS / Money & Monetary Policy; BUSINESS & ECONOMICS / Development / Economic Development; Banks and banking, Cooperative -- Developing countries; Financial services industry -- Developing countries; Income distribution -- Developing countries